2014
DOI: 10.1016/j.enmm.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of olive mill based wastewater by means of magnetic nanoparticles: Decolourization, dephenolization and COD removal

Abstract: Please cite this article in press as: Nassar, N.N., et al., Treatment of olive mill based wastewater by means of magnetic nanoparticles: Decolourization, dephenolization and COD removal. Environ. Nanotechnol. Monit. Manag. (2014), http://dx. a b s t r a c tOlive mill wastewater (OMW) is an environmental concern that has been highlighted as a serious environmental problem in the Mediterranean basin countries because of its high organic load and phytotoxic and antibacterial phenolic compounds, which resist biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…According to several studies [82,[98][99][100], nanoparticles can enter living organisms by ingestion and inhalation and cause toxic effects in organs and tissues. Moreover, the nanoparticles can interact with pollutants in environmental applications and act as carriers of them into aquatic ecosystems [82,[101][102][103]. In this context, the immobilization of MNPs onto high-surface-area supports represents an environmentallyfriendly solution which would preserve their unique properties, avoiding their potential negative effects.…”
Section: Supported Ferromagnetic Nanoparticles and Magnetic Compositesmentioning
confidence: 99%
“…According to several studies [82,[98][99][100], nanoparticles can enter living organisms by ingestion and inhalation and cause toxic effects in organs and tissues. Moreover, the nanoparticles can interact with pollutants in environmental applications and act as carriers of them into aquatic ecosystems [82,[101][102][103]. In this context, the immobilization of MNPs onto high-surface-area supports represents an environmentallyfriendly solution which would preserve their unique properties, avoiding their potential negative effects.…”
Section: Supported Ferromagnetic Nanoparticles and Magnetic Compositesmentioning
confidence: 99%
“…Predescu and Nicolae (2012) synthesized a nano-composite particle from γ-Fe 2 O 3 with AMBERLITE cationic exchange resin and reported that the nano-composite material had remarkable adsorption efficiency in the removal of some toxic metal ions as Zn, Cu, Cr. Nassar et al (2014) Nanostructured graphite oxide, silica/graphite oxide composites and silica nanoparticles were investigated for the removal of the heavy metal ions from aqueous solutions by a batch adsorption method (Sheet et al 2014). The results revealed that the adsorption of heavy metals by nanostructured graphite oxide was observed in the following order: nickel > zinc > lead > cadmium > chromium.…”
Section: Polymeric/inorganic Nanoparticlementioning
confidence: 99%
“…Recently, because of their unique and unexpected chemical and physical properties compared to their counterparts, iron‐based nanoadsorbents have emerged as an alternate source for conventional adsorbents. Properties such as excellent magnetic behaviour, chemical stability, biocompatibility, amphoteric surface activity, high adsorption capacity, enhanced catalytic activity, and dispersability have been reported . Further, several researchers have reported on the employment of iron‐based nanoadsorbents in removing various pollutants from wastewater .…”
Section: Introductionmentioning
confidence: 99%